Possible Implications for Improved Osteogenesis? The Combination of Platelet-Rich Fibrin With Different Bone Substitute Materials - Blatt, Sebastian; Thiem, Daniel G. E.; Kyyak, Solomiya; Pabst, Andreas; Al-Nawas, Bilal; Kämmerer, Peer W. (Frontiers in Bioengineering and Biotechnology, 2021)
Bone substitute materials (BSM) are widely used in oral regeneration, but sufficient angiogenesis is crucial for osteogenesis. The combination of BSM with autologous thrombocyte concentrations such as platelet-rich fibrin (PRF) may represent a clinical approach to overcome this limitation. This study analyses the early influence on osteoblast (HOB) in vitro. Here, four different BSM (allogeneic, alloplastic and xenogeneic origin) were combined with PRF. After incubation with osteoblasts for 24h, cell viability, migration and proliferation were assessed. Next, marker of proliferation, migration and differentiation were evaluated on gene and protein levels in comparison to the native BSM and osteoblast alone. Addition of PRF increased viability for both xenogeneic BSM (p=0.0008, p=0.032 respectively) in comparison to HOB and vs. native BSM (p=0.008) and led to a tendency for increased cell proliferation and migration for all BSM (each p>0.05). On gene basis, allogeneic and alloplastic BSM displayed a significant increased RUNX2 expression (each p=0.050). Expression of alkaline phosphatase for alloplastic (p=0.050) and collagen-1 for xenogeneic BSM (p=0.05) were significantly increased in combination with PRF. In addition, bone morphogenic protein was expressed significantly higher when xenogeneic material where combined with PRF in comparison to HOB alone (each p=0.05). In summary, the combination of PRF with different bone substitute materials increases initial viability and may influence early proliferation and migration potential of osteoblast via RUNX2, alkaline phosphatase, collagen, and BMP2 especially in combination with alloplastic and xenogeneic BSM. Biofunctionalization of BSM using PRF might improve osteogenesis and extend the range of indications.